Assessing the potential of low-carbon technologies in the German energy system. (15th May 2020) - Kumar, Subhash; Loosen, Maximilian; Madlener, Reinhard
Abstract: With the introduction of its energy concept in 2010, the German government set ambitious targets for the country's energy and climate policy. According to this concept, greenhouse gas (GHG) emissions will have to be reduced by 80% by 2050, as compared to 1990 levels, and renewables will have to supply 80% of all electricity needs by the same year. Additionally, Germany has decided to phase out its nuclear energy by 2022. This study investigates the possible components to achieve these targets. The analysis is based on an hourly simulation model EnergyPlan. Three scenarios are developed to investigate the potential development of the German energy supply system until 2050. The results indicate renewable shares of 92% and 81% for scenarios B and A, respectively, by 2050 compared to 69% in the reference scenario. The proposed renewable energy system is even found to involve lower costs than today's energy system (i.e. total annual cost for scenario B is € 260 bn compared to € 293 bn in the reference scenario). The results show that a massive decarbonization of the German energy system until 2050 seems technically and economically feasible, if smart grid costs are disregarded and if this sustainable energy transformation is accompanied by political and genuine public willingness to actually achieve the set goals and take the necessary steps. Highlights: In this paper low carbon technologies are used to estimate the CO2 mitigation potential in Germany. The EnergyPlan model has been used in this work. Three scenarios are developed by considering different policies for Germany. The result shows 90% CO2 emission reduction and 92% renewable generation possible in B scenario.